2021
DOI: 10.29328/journal.ivs.1001028
|View full text |Cite
|
Sign up to set email alerts
|

Pig raising practices by unprivileged, ethnic people in Bangladesh

Abstract: We interviewed 207 pig raisers from seven different districts of Bangladesh to explore their practices related to their pig farming. We used structured questionnaires to interview the pig raisers and used descriptive statistics for analysis. Most of the pig raisers (54%) were illiterate. 50% (104) of them had a monthly income of less than 10000 BDT and 60% (124) were landless. Most of the pig raisers (92%, 191) were rearing local breed and 67% of them were practicing semi-scavenging system. As feed source 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
2
1
Order By: Relevance
“…This will require training farmers on the prevention and control of ectoparasites in pigs. These results differed from those reported by Kagira et al [ 15 ] in Kenya and Islam et al [ 5 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This will require training farmers on the prevention and control of ectoparasites in pigs. These results differed from those reported by Kagira et al [ 15 ] in Kenya and Islam et al [ 5 ].…”
Section: Discussioncontrasting
confidence: 99%
“…It can also provide livelihood and employment [ 3 ]. Most pigs are raised by smallholders in extensive, semiextensive, and intensive systems [ 4 , 5 ]. Pig farming requires in general too much attention related to biosecurity measures, control, and management.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, respondents in the study did not support the preventive measure of maintaining a standard distance between the home and shed (Park, 2009, p. 66). Few respondents reported (2.1%–13.0%) maintaining this 15‐m standard; similar practices were observed in smallholder farmers in Bangladesh (Ausraful et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…Economic status, education, or several socio-cultural values determine farm and household sanitation in farming communities. However, only 12.3 percent of respondents were found to have maintained a standard distance between home and shed in the study, and similar practice was observed in Bangladesh [37]. But in another study in Bangladesh, nearly half (43.0%) of the farms were attached to their houses [35].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 73%